D-dimer as a marker for cardiovascular and arterial thrombotic events in patients with peripheral arterial disease - Kleinegris, Marie-Claire F.; Cate, Hugo ten; ten Cate-Hoek, Arina J. (Thrombosis and Haemostasis, 2013)
Peripheral artery disease (PAD) is associated with an increased risk for cardiovascular events. D-dimers are a marker for hypercoagulability and are linked with thrombotic events in patients with venous as well as arterial thrombosis. The predictive value of plasma D-dimer levels in relation to cardiovascular events in patients with PAD is not unambiguously established. It was our objective to gather evidence evaluating the value of D-dimer as a predictor of arterial thrombotic events patients with PAD. The Pubmed, Embase, and Cochrane databases were searched (January 1980-November 2012), and 65 abstracts were found. The strategy was supplemented with manual review of reference lists. Case-control, cohort or prospective cohort studies that measured fibrin D-dimer in patients with PAD, were included. Studies were excluded if there was no follow-up for arterial thrombotic events or when no specific information on D-dimer was available. The search yielded 10 studies for our analysis, comprising 2,420 patients with PAD, with a total of 1,036 cardiovascular events in 10,599 patient-years. Two studies with a follow-up of one year showed that fibrin D-dimer predicts both deterioration of PAD and subsequent thrombotic events. Five out of six studies with a median follow-up of 2–4 years revealed that an increased D-dimer is predictive of various arterial thrombotic events including mortality. Two studies with a longer follow-up (over 6 years) did not show an independent association between increased D-dimer levels, arterial thrombotic events and CVD mortality. In conclusion, an increased D-dimer appeared to be independently associated with a two times increased risk of near-term cardiovascular events (relative risk 2.30, 95% confidence interval 1.43–3.68). However formal meta-analysis was only feasible for four out of 10 included studies. Due to the extended heterogeneity of the included studies cautious interpretation of these data is warranted.
Keywords: Peripheral arterial disease; D-dimer; fibrin degradation products; intermittent claudication; arterial thrombotic events